The Effect of Smoking on Response to Tumour Necrosis Factor-Alpha Inhibitor Treatment in Psoriatic Arthritis Patients: Results from the TURKBIO Registry - Yarkan, Handan; Kenar, Gokce; Capar, Sedat; Can, Gercek; Zengin, Berrin; Akar, Servet; Onen, Fatos (Wiley, 2018)
[Abstract Not Available]
Annual Meeting of the American-College-of-Rheumatology (ACR) and Association-for-Rheumatology-Health-Professionals (ARHP) -- OCT 19-24, 2018 -- Chicago, IL